2022
DOI: 10.1371/journal.pone.0266926
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, sedentary behavior, and physical activity in Brazilian adolescents: Achievement recommendations and BMI associations through compositional data analysis

Abstract: Physical activity, sedentary behavior (SB), and sleep are habitual human behaviors (HHB) which are modifiable throughout the different life phases. Therefore, it is necessary to analyze how the time distribution throughout the day among HHB may be associated with body mass index (BMI). These results could provide inferences which can guide interventions that trigger changes in adolescent behaviors in favor of their health. The objective of this study was to verify the proportion of adolescents who meet the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
2
0
6
Order By: Relevance
“…Vários estudos têm utilizado essa metodologia (Barreira et al, 2018;Chaput et al, 2015;Domingues et al, 2022;Dumuid et al, 2018a;Lin et al, 2018;Mcneil et al, 2015;Tudor-Locke et al, 2014 devido à facilidade de uso, por causar menos incômodo aos participantes. Dessa forma, se minimiza os problemas ocasionados pela movimentação do dispositivo de um local para outro do corpo (Tudor-Locke et al, 2015), o que amplia as possibilidades de adesão ao protocolo.…”
Section: Composição Do Dia E Mensuração Dos Chhunclassified
See 2 more Smart Citations
“…Vários estudos têm utilizado essa metodologia (Barreira et al, 2018;Chaput et al, 2015;Domingues et al, 2022;Dumuid et al, 2018a;Lin et al, 2018;Mcneil et al, 2015;Tudor-Locke et al, 2014 devido à facilidade de uso, por causar menos incômodo aos participantes. Dessa forma, se minimiza os problemas ocasionados pela movimentação do dispositivo de um local para outro do corpo (Tudor-Locke et al, 2015), o que amplia as possibilidades de adesão ao protocolo.…”
Section: Composição Do Dia E Mensuração Dos Chhunclassified
“…Contudo, um estudo de revisão recente mostra uma baixa prevalência (<15%) de crianças e adolescentes que atendem as recomendações de TT (indicativo de CS), AFMV e sono concomitantemente (Rollo;Antsygina;Tremblay, 2020;Tapia-Serrano et al, 2022). O mesmo tem sido confirmado por outros estudos observacionais realizados em diversos países como Austrália, China, Colômbia, Finlândia, Índia, Quênia, Portugal e África do Sul (Roman- et al, 2016), Japão (Tanaka et al, 2019(Tanaka et al, , 2020, República Tcheca (Jakubec et al, 2020;Rubín et al, 2020), Estados Unidos (Laurson et al, 2014;Laurson;Lee;Eisenmann, 2015;Roman-Viñas et al, 2016), Canadá Roberts;Thompson, 2017;Roman-Viñas et al, 2016), Reino Unido (Pearson;sherar;Hamer, 2019;Roman-Viñas et al, 2016) e no Brasil (Da Costa et al, 2020;Domingues et al, 2022;Roman-Viñas et al, 2016).…”
Section: Composição Do Dia E Mensuração Dos Chhunclassified
See 1 more Smart Citation
“…Until recently, a group of studies used CoDA to examine the relative relationship between accelerometer-measured 24-h movement and body mass index (BMI) and estimate the differences in BMI z-score when time in 24-h movement was reallocated among children and adolescents. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Most studies found that participants with a greater amount of MVPA time, relative to other behaviours, tend to have lower adiposity measures 15 , 16 , 19 , 23 , 24 , 27 , 28 and participants with a greater amount of SED time, relative to other behaviours, tend to have higher adiposity measures. 15 , 16 , 22 , 24 , 26 Findings from most compositional isotemporal substitution studies suggested that lower adiposity was estimated when time was reallocated from a fixed duration of sleep, SED, and LPA to an equivalent duration of MVPA and from SED or LPA to sleep, whereas higher obesity was observed for opposite reallocation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, compositional data analysis (CoDA) has become popular, as the technique takes into account all components of a whole simultaneously by a set of logs, while being able to circumvent some common problems in traditional statistics (e.g., covariance) and also investigates the association between different temporal components and health outcomes through modeling [ 18 , 21 , 22 ]. A few studies have examined the relationships between 24-h behaviours and health outcomes using CoDA [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Even then, apparently all research studies based on CoDA are single-year cross-sectional studies that focused on children and adults, with relatively fewer focusing on preschoolers.…”
Section: Introductionmentioning
confidence: 99%